Clay Mineralogy of Soils Developed from Granite-Gneiss of Kurnool District in Andhra Pradesh - M.V.S. Naidu, P.V. Geetha Sireesha (Journal of the Indian Society of Soil Science, 2015)
The soils of Banaganapalle mandal in Kurnool district of Andhra Pradesh were developed from dolomite and granite-gneiss under semi-arid climate at an average elevation of 243 m above mean sea level (msl). These soils were investigated for clay mineralogy using X-ray diffraction technique and chemical analysis of clay. The clay films invariably exhibited characteristic peaks of smectite, kaolinite and illite. Semi-quantification analysis of clay fractions based on relative areas under corresponding peaks indicated that pedons 1, 2, 3 and 5 were dominated by smectite followed by kaolinite, illite, feldspars and quartz while pedons 4 and 7 were dominated by kaolinite followed by smectite, illite, feldspars and quartz. The formation of smectite suggests that these soils were formed through a progressive landscape reduction process and appears to be under basic environment, impeded drainage and water logging conditions. The dominance of kaolinite may be due to their well-drained conditions. However, use and management of these soils for agricultural production require an understanding of their clay mineralogy.